Comparação do potencial antibacteriano dos óleos essenciais de orégano e tomilho contra cepas de Klebsiella Pneumoniae e incorporação em membranas de quitosana para o tratamento de lesões por pressão - Silva, Sonaly de Lima (2023)
Bacteria may be the initial cause of certain pathologies as well as a secondary agent responsible for the development of complications such as pressure sore infections. And the exacerbated use of antimicrobials for the treatment of these lesions may contribute to the selection of new bacterial strains resistant to traditional antimicrobials. Thus, the antibacterial potential of oregano essential oil (OEO) was compared with that of thyme essential oil (TEO) on strains of Klebsiella pneumonie, as well as their incorporation into scaffold-type chitosan membranes for the treatment of pressure ulcers. To this end, the chemical composition of the essential oils (EOS) was determined by Gas Chromatography Coupled with Mass Spectrometry (GC-MS), as well as the Minimum Inhibitory Concentration (MIC), the Minimum Bactericidal Concentration (MBC) by micro dilution in Mueller Hinton broth, and the Minimum Adherence Concentration (MAC), using test tubes. Turning to the combined use of EOs with antimicrobials, the association study was developed by the infusion dise method. Finally, and after the isolated and comparative analysis of the oils, chitosan membranes were developed, scaffolds type, incorporated with these EOs. After making the membranes, the chemical, physical and biological structure was analyzed by optical microscopy (OM), Fourier Transform Infrared Spectroscopy (FTIR), thermogravimetry (TGA), degree of swelling (DS), enzymatic biodegradation and antimicrobial activity. Thus, the majority compounds of the EOS- carvacrol, para-cymene and thymol were obtained. For OEO, an MIC50 of 128µg/ml. and MBC between 512 µg/ml. - 256 µg/m was verified. While for TEO, an MIC50 of 256µg/mL and MBC of 256 µg/ml was observed for most of the tested strains. Regarding the ability to inhibit biofilm formation, neither the OEO, nor the TEO, nor the 0.12% chlorhexidine digluconate were able to do so. In the association study, a synergism of the two EOs was observed with ampicillin and gentamicin. Regarding the characterization of the membranes, a porous structure and homogeneous surface was observed by MO. In the FTIR test it was possible to confirm the incorporation of the EOs in the chitosan membrane. The TGA results indicate that there was no significant change in temperature for the beginning of mass loss by the isolated membranes, as well as for those incorporated with OEs. All the membranes presented a high degree of intumescence. Regarding the biodegradation test, it was observed that the samples submerged in lysozyme showed a greater loss of mass. And from the evaluation of the antimicrobial activity, it was obtamed that the pure and incorporated membranes presented the capacity to inhibit the growth of Klebisiella pneumoniae bacteria. Thus, it is concluded that the EOs present antimicrobial action on Klebsiella pneumoniae strains and when incorporated into chitosan membranes they represent a promising therapeutic modality for future treatment of pressure ulcers